Analisis Earning Per Share, Return On Assets, Return On Equity, Dan Debt To Equity Ratio Terhadap Harga Saham - Nandya Eka Prestanti; Suhendro, Suhendro; Masitoh, Endang (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
The purpose of this study was to determine the effect of earning per share, return on assets, return on equity, and debt to equity ratio to the price of shares in the sector of consumption on the Stoctk Exchange. This research is a quantitative type. The sample in this research is sector of consumptiom that listed in Indonesia Stock Exchange (BEI). The sample was chosen using purposive sampling method, with the number of 28 (twenty eight) companies. Data analysis techniques use classical assumption test, multiple linear regression analysis and hypothesis test. This analysis is done by using SPSS program. This research shows that Earning Per Share, Return On Assets, Return On Equity, and Debt To Equity Ratio partially have no significant effect on stock price, while simultaneously have a significant effect on stock price.